Corporate social responsibility in construction industry: A comparative study between UK and Turkey. Issue 2 (3rd May 2016) - Ulutaş Duman, Dilek; Giritli, Heyecan; McDermott, Peter
Abstract : Purpose: – Corporate social responsibility (CSR) has evolved to an important agenda for many industries and its scope has been widened from the responsible business to strategic decisions. Therefore, the purpose of this paper is to investigate the concept of CSR from the perspective of construction industry by questioning CSR awareness, CSR activities and CSR integration with a comparative case study between UK and Turkey. Design/methodology/approach: – Conducting comparative and qualitative research using a case study methodology, this study sets the context for understanding differences in these two countries as to how CSR is perceived and put into practice by selected case firms. Findings: – The results revealed that construction companies are aware of the increasing importance of the CSR; however, company scale and the characteristics of the country have great impact on CSR preferences. Despite the differences in the approaches all firms take with regard to CSR domains and CSR types, ethical domain and the social orientation have become prominent for CSR initiatives in both the UK and Turkey. Originality/value: – This study provides the empirical evidence for the understanding and integration of the CSR concept in the construction industry; shed light on missing knowledge about CSR integration and serves as a source for further in-depth researches on CSR.